Faktor-Faktor yang Berhubungan dengan Jumlah Kelahiran Hidup pada Ib-Ibu di Wilayah Kerja Puskemas Masbagik, Lombok Timur - Kartika Dewi; Yoga Pamungkas Sussani; Gede Wira Buanayuda (Unram Medical Journal, 2022)
Background: Fertility as a demographic’s term is defined as the real reproductive result of a woman or group of women. Fertility is influenced by several factors, where these factors play a role in the rate of population growth. Factors that influence fertility, consist of non-demographic factors and demographic factors. There is also an intermediate variable, factors that influence the start of sexual intercourse to the occurrence of pregnancy. Aim of this study is to evaluate correlations between mother’s age when giving first birth, age when giving recent birth, level of education, occupation and number of live birth on mother’s in the work area of ??Masbagik Primary Health Care Center Methods: This research is a quantitative study and uses a correlative research design with a cross-sectional approach on secondary data, taken from the medical records of patients who have given birth in the working area of ??the Masbagik Primary Health Care Center. Result: In this study, all factors studied had p<0.05 and it indicates that there is a meaningful relationship between the factors studied and the number of live births. Where educational factors as well as the age of mother first childbirth have a negative correlation relationship and the job factor and the age of the mother during childbirth has a positive correlation. Conclusion: There were significant correlation between factors that are studied with the total of live birth the mothers had on the work area of Masbagik Primary Health Care Center.